High Cesarean Section Rates during Labor Induction in Low Risk, Late-Term Cephalic Pregnancies in a Tertiary Centre - Neslihan Erkal; Metin Kaba; Yeliz Akpinar Mayir; Fatma Elif Isik Eryilmaz (Clinical and Experimental Obstetrics & Gynecology)
Background: The cesarean section rate is high in countries such as Türkiye, Egypt, and Brazil. The aims of this study were to determine whether the cesarean section rate during labor induction is high in late-term cephalic pregnancies and to evaluate the related factors. Methods: This retrospective descriptive study was conducted with 254 patients with a cephalic fetal presentation who were admitted in the labor unit of a tertiary center for induction of labor (IOL) at ≥41 0/7 weeks of gestation. The patients were evaluated in terms of demographic characteristics, Bishop score, labor induction method (dinoprostone or oxytocin administration), IOL duration, vaginal delivery rate, cesarean section rate, indication for cesarean delivery, 5-min Apgar score, fetal requirement for neonatal resuscitation, oxygen treatment, and neonatal intensive care unit admission. Results: The study population comprised 254 patients, of whom 181 (71.3%) had a vaginal delivery and 73 (28.7%) had a cesarean delivery. To evaluate the factors that affect labor induction failure and cesarean indication, the patients were divided into two groups: the nulliparous (n: 122) and multiparous (n: 132). The cesarean section rates in the nulliparous and multiparous groups were 44.3% (n: 54/122) and 14.4% (n: 19/132), respectively. According to the multivariate logistic regression, being nulliparous, having a male fetus were found to be the associated risk factors for cesarean delivery (p < 0.05). Conclusions: The study results suggest that the cesarean section rate during labor induction is higher in low-risk, late-term cephalic pregnancies. Nulliparity, male fetal sex were risk factors for cesarean delivery.